PELAKSANAAN PERJANJIAN KEBERANGKATAN IBADAH UMROH ANTARA CALON JAMAAH UMROH DENGAN PT. HIJRAH HARAMAIN DI KOTA MEDAN - A. M, Wita Trisnawati; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
As is known that Islam is the majority religion in Indonesia, which means it has the most number of followers. In Islam it has five pillars of Islam which are obligatory to be executed by each of its followers. The pillars of Islam consist of two sentences of creed, establish prayer, undergo fasting, paying zakat, and performing hajj and umroh. In accordance with Law Number 13 of 2008 concerning the Implementation of Hajj, that the pilgrimage and pilgrimage travel can be carried out individually and in groups through the organization of pilgrimage and pilgrimage trips carried out by the government or travel agencies that have obtained permission from the Minister of Religion. Every prospective pilgrim who wants to perform Umrah cannot go alone without going through a travel agency which currently stands a lot, one of which is a pilgrimage company located in the city of Medan, PT. Hijrah Haramain. The implementation of the departure of prospective Umrah pilgrims conducted by PT. Hijrah Haramain with the prospective pilgrims used an agreement. However, the implementation of this agreement does not work as it should. PT. Hijrah Haramain failed to appoint prospective Umrah pilgrims because of PT. Hijrah Haramain itself. The purpose of this thesis is: First, to know the implementation of the umroh worship departure agreement executed by PT. Hijrah Haramain, Second, to find out the accountability of PT. Hijrah Haramain due to the cancellation of the departure of prospective pilgrims.This type of research can be classified in the type of sosiological juridical research. The research was conducted at PT. Hijrah Haramain in Medan City. Sosiological law research uses primary data and secondary data, while population and sample are the parties related to the problem studied in this research. Technique of collecting data in this research by interview and literature study.From the results of research problems there are two main things that can be concluded. First, PT. HIjrah Haramain did not implement the agreement as agreed with the prospective Umrah pilgrims, namely the default that had occurred by PT. Hijrah Haramain by not dispatching prospective Umrah pilgrims. Second, PT. Hijrah Haramain did not pay compensation as a form of his responsibility for the cancellation of the departure of prospective Umrah pilgrims.Key Words: Umrah – Agreement – Default - The Organizer Of The Umrah Service – Prospective Umrah Pligrims